Some aspects in photogrammetry education at the department of geodesy and cadastre of the VGTU - Ruzgienė, Birutė (Geodesy and Cartography, 2012)
Th e education in photogrammetry is very important when applying photogrammetric methods for the terrain mapping purposes, for spatial data modelling, solving engineering tasks, measuring of architectural monuments etc. During the time the traditional photogrammetric technologies have been changing to modern fully digital photogrammetric workflow. The number of potential users of the photogrammetric methods tends to increase, because of high-degree automation in photographs (images) processing. The main subjects in Photogrammetry (particularly in Digital Photogrammetry) educational process are discussed. Different methods and digital systems are demonstrated with the examples of aerial photogrammetry products. Th e main objective is to search the possibilities for training in the photogrammetric measurements. Special attention is paid to the stereo plotting from aerial photography applying modifi ed for teaching analytical technology. The integration of functionality of Digital Photogrammetric Systems and Digital Image Processing is analysed as well with an intention of extending the application areas and possibilities for usage of modern technologies in urban mapping and land cadastre. Th e practical presentation of photos geometry restitution is implemented as signifi cant part of the studies. The interactive teaching for main photogrammetric procedures and controlling systems are highly desirable that without any doubt improve the quality of educational process.Kai kurie fotogrametrijos mokymo VGTU Geodezijos ir kadastro katedroje aspektaiSantrauka. Fotogrametriniai metodai plačiai taikomi sudarant topografi nius žemėlapius, kartografuojant architektūrinius paminklus ir kt. Aerofotografavimo darbai, kurių rezultatais remiamasi konstruojant aerofototopografi nes nuotraukas, ir ypač ortofotografi nius žemėlapius, nenutrūkstamai bus plėtojami, o aerofotografi nės produkcijos vartotojų vis gausės. Siekiant fotogrametrinius metodus efektyviai ir visapusiškai taikyti kaupiant informaciją, kurią teikia fotonuotraukos (skaitmeninės ar analoginės), reikia kvalifi kuotų specialistų, gerai išmanančių šiuolaikinės fotogrametrijos principus, mokančių taikyti skaitmeninės fotogrametrijos metodus. Šiuo tikslu nagrinėjama pasiūlyta fotogrametrijos modulio anotacija, analizuojami pagrindiniai mokymo aspektai, buvo taikomos aerofotonuotraukų apdorojimo sistemos bei rekomenduojamos mokymo formos.First published online: 03 Aug 2012